Antiviral activity of modified oligonucleotides in human lymphoid cells infected with a strain of HIV‐1 - L. G. Gotfrid; A. S. Pavlova; M. S. Kupryushkin; I. A. Pyshnaya; N. M. Gashnikova (Юг России: экология, развитие)
Aim. To investigate the cell entry and antiretroviral properties of modified oligodeoxyribonucleotides targeting highly conserved regions of the HIV‐1 genome: the study was conducted using modified oligonucleotides containing phosphorothioate, phosphorylguanidine or dodecyl moieties.The ability of oligonucleotides to inhibit the virus was studied using a model of lymphoid culture of human MT4 cells infected with a characterised high‐productive strain of HIV‐1 belonging to the subtype A6 genovariant widely spread in the Russian Federation. The entry of oligonucleotides into MT4 cells was assessed by confocal microscopy.It was shown that phosphorothioate‐ and dodecyl‐containing oligonucleotides are able to penetrate inside cells without the use of any additional transfection agents. It was found that phosphorothioate oligonucleotides transfected in duplex with dodecyl‐containing derivatives were localized inside the cell in the nucleus and nucleolus and were able to inhibit the reproduction of a highly productive HIV‐1 strain. A 50% toxic dose (TC50) and a 50% inhibitory concentration (IC50) were determined for the oligonucleotide derivatives studied, the value of which was less than 0,5 μM in the case of phosphorothioate oligonucleotides.The data obtained indicate the ability of the modified oligonucleotides studied to be used as potential antiviral agents against HIV‐1.